Hydrogen solubility, interfacial tension, and density of the liquid organic hydrogen carrier system diphenylmethane/dicyclohexylmethane - Jander, Julius Hans; Schmidt, Patrick; Giraudet, Cédric; Wasserscheid, Peter; Rausch, Michael Heinrich; Fröba, Andreas Paul (International Journal of Hydrogen Energy, 2021)
In the present study, physico-chemical properties of the liquid organic hydrogen carrier (LOHC) system diphenylmethane/dicyclohexylmethane in the presence of dissolved hydrogen are presented for temperatures up to 523 K and pressures up to 10 MPa. Solubility of hydrogen, interfacial tension, and liquid density were measured by the isochoric saturation method, the pendant-drop method, and vibrating-tube method, respectively, which are realized in two experimental setups. The solubility of hydrogen increases with increasing temperature and pressure. For the fully hydrogenated dicyclohexylmethane, it is about 50% higher than for the non-hydrogenated diphenylmethane and similar to that of a mixture from a deliberately stopped hydrogenation process containing also partially hydrogenated cyclohexylphenylmethane. While the interfacial tension decreases slightly with increasing hydrogen pressure at constant temperature, the density remains approximately constant. The latter properties obtained for different mixtures with similar degree of hydrogenation show that the influence of the presence of cyclohexylphenylmethane is small.
CRIS-Team Scopus Importer:2021-04-30
Keywords: Density; Dissolved hydrogen; Interfacial tension; LOHC systems; Solubility